Potencial e lacunas de produtividade em soja no Brasil: uma análise pela metodologia do “Global Yield Gap Atlas” - Richter, Gean Leonardo (2021)
In 2050 the world population will reach close to 10 billion inhabitants. And Brazil is of great importance due to the production of food, especially with the soybean, where it is the largest producer in the world. And for that, the yield potential is used to make decisions about agricultural policies, due to the growing demand for food and energy in many countries. The objective was to estimate the yield potential and gap in soybean in Brazil. And define the loss of yield due to the delay in the sowing date for all of Brazil. Selection of data sources and quality control are based on guidelines provided in the Global Yield Gap Atlas protocols, using calibrated models and the best available data on harvested soybean area, meteorological data, actual farmer yields and a spatial framework for the specific locations (regional and national levels). We conclude that the yield potential ranges from 5.7 to 7.5 Mg ha-¹, and the average is 6.7 Mg ha−¹. The water limited yield potential ranges from 3.1 to 6.9 Mg ha-¹ and the average is 5.5 Mg ha−¹ and the actual yield is 3.0 Mg ha−¹ for Brazil. The yield gap ranges from 2.7 to 4.6 Mg ha-¹, and the average is 3.7 Mg ha-¹. Dividing the yield gap into management gap and water gap we obtain values of 2.5 Mg ha-¹ and 1.2 Mg ha-¹, respectively, for all of Brazil. Finally, in the 5 soybean macroregions it is possible to identify the yield lost with the delay in the sowing date for all of Brazil.